Smart Alarm for Factories & Inventories (IoT) - Ali Ghazi Abu Saleh; Abdallah Wael Mustafa (My University, 2021)
In many warehouses or factories, as it’s usually closed or under- ground, keeping the humidity and temperature in the recommended values range is a major problem. Moreover fire detection is a key player in keeping the factory working, also In industry field 80% of the acci- dents are caused by humans actions. In this project, we will apply the concept of the internet of things (IoT) into the Factories/warehouses alarms’ systems and Fuzzy Logic Controller approach . Our goal is to provide a new alarm monitoring system that keeps tracking the value for many sensors and take action in intelligent way if something went wrong in the factory/warehouse. In this project, our core control inputs will be the current value of temperature and humidity using a DHT11 sensor, flame detection using a flame sensor, and movement detection using a distance sen- sor HC-SR04, then based on the current values that are feeding the core unit and the thresholding values the user sets the core unit will take action starting the fan for decrease the temperature/ humidity, starting the pump in case the flame sensor detects a fire or starting an electric hood to decrease the O2 percentage in the air in the fac- tory/warehouse, or finally triggering an alarm if a movement detection, all the outputs will be based on fuzzy logic Mamdani approach. This project will be controlled in 2 ways, either by the remote con- trol which requires the user to be close to the control unit (IR based) or it can be controlled by the mobile application which we will connect the core to the WIFI wirelessly. The intelligent behaviour is applied by using Fuzzy Logic , and one of the action run the Fan at specific speed , and this speed is de- termined by the fuzzy logic depends on current temperature and the humidity . The report discusses applying IoT concept into smart alarms’ sys- tems, presents the communication over the WIFI network & IR remote from one side and the hardware core from other side.The programming tools and platforms that was used to implement the project are: C++ for Arduino Uno.In addition to RemoteXY platform for implementing the Mobile application.